Are levels of perfluoroalkyl substances in soil related to urbanization in rapidly developing coastal areas in North China?. (April 2015) - Meng, Jing; Wang, Tieyu; Wang, Pei; Zhang, Yueqing; Li, Qifeng; Lu, Yonglong; Giesy, John P.
Abstract: Concentrations of 13 perfluoroalkyl substances (PFASs) were quantified in 79 surface soil samples from 17 coastal cities in three provinces and one municipality along the Bohai and Yellow Seas. The ∑PFASs concentrations ranged from less than limitation of quantification (LOQ) to 13.97 ng/g dry weight (dw), with a mean of 0.98 ng/g dw. The highest concentration was observed along the Xiaoqing River from Shandong province, followed by that from the Haihe River in Tianjin (10.62 ng/g dw). Among four regions, ∑PFASs concentrations decreased in the order of Tianjin, Shandong, Liaoning and Hebei, which was consistent with levels of urbanization. Fluorine chemical industries allocated in Shandong and Liaoning played important roles in terms of point emission and contamination of PFASs, dominated by perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS). Intensive anthropogenic activities involved in urbanization possibly resulted in increasing releases of PFASs from industrial and domestic sources. Highlights: PFASs were detected in the soil of rapidly developing coastal regions in China. PFAS concentrations ranged from LOQ to 13.97 ng/g dw, with a mean of 0.98 ng/g dw. Higher concentrations of PFASs correspond to higher levels of urbanization. Existence of fluorine industry induced PFAS pollutions dominated by PFOA and PFOS. Intensive urbanization caused increasing emission of industrial and domestic PFASs. Abstract : Among urban, suburban and rural areas in the coasts, soils from urban area showed high degrees of PFASs contamination with the existence of industrial emissions dominated by PFOA and PFOS.